2016
DOI: 10.1590/1516-4446-2016-1976
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response in the treatment of moderate depression

Abstract: Objective: To identify neurocognitive and sociodemographic variables that could be associated with clinical response to three modalities of treatment for depression, as well as variables that predicted superior response to one treatment over the others. Method: The present study derives from a research project in which depressed patients (n=272) received one of three treatments -long-term psychodynamic psychotherapy (n=90), fluoxetine therapy (n=91), or a combination thereof (n=91) -over a 24-month period. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In a longer treatment trial, Bastos et al ( 25 ) examined the relationship between executive function performance and response to 24 months of treatment with Fluoxetine ( n = 91), psychodynamic psychotherapy ( n = 90) or a combination thereof ( n = 90). The largely negative results were complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a longer treatment trial, Bastos et al ( 25 ) examined the relationship between executive function performance and response to 24 months of treatment with Fluoxetine ( n = 91), psychodynamic psychotherapy ( n = 90) or a combination thereof ( n = 90). The largely negative results were complex.…”
Section: Resultsmentioning
confidence: 99%
“…The largely negative results were complex. Of 14 cognitive variables, higher scores on two (WAIS-III, Letter Number Sequencing and Matrix Reasoning) were associated with better response across all three treatments (Fluoxetine, psychodynamic psychotherapy and the combination) and higher scores on one (WAIS-III, Similarities) was associated with poorer response ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beaudreau et al (2015) reported that impaired cognitive flexibility predicted poorer therapeutic response (problem-solving therapy and supportive therapy) in older depressed patients. Similarly, Bastos et al (2017) found that better performance on measures of cognitive flexibility/executive functioning predicted better response to psychotherapy (psychodynamic) and medication or a combination of the two. These findings are also consistent with Mason et al's (2016) recent review reporting that connections from the prefrontal cortex appear to be an important predictor of outcome in CBT.…”
Section: Introductionmentioning
confidence: 90%
“…It seems that psychodynamic treatment which focuses mainly on basic relational and emotional processes does not interact with these variables. Similar results of missing relationships between sociodemographic variables and the outcome of psychodynamic psychotherapy were found in the treatment of depression (Bastos, Guimaraes, & Trentini, 2017), social anxiety disorder (Wiltink et al, 2016), and deliberate self-poisoning (Guthrie et al, 2003). However, these findings are not entirely consistent.…”
Section: Discussionmentioning
confidence: 72%